2019
DOI: 10.3389/fnins.2019.00450
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Profiles of N-Acylethanolamines in Goldfish Brain and Gastrointestinal Tract: Possible Role of Feeding

Abstract: N -acylethanolamines (NAEs) are a family of endogenous lipid signaling molecules that are involved in regulation of energy homeostasis in vertebrates with a putative role on circadian system. The aim of this work was to study the existence of daily fluctuations in components of NAEs system and their possible dependence on food intake. Specifically, we analyzed the content of oleoylethanolamide (OEA), palmitoylethanolamide (PEA), stearoylethanolamide (SEA), their precursors (NAPEs), as well as the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 56 publications
(121 reference statements)
1
0
0
Order By: Relevance
“…During this resting and fasting states, animals obtain energy from increasing the hepatic fatty oxidation ( Ribas-Latre and Eckel-Mahan, 2016 ), metabolic process that is promoted by PPARα in mammals ( Chen and Yang, 2014 ; Liu et al, 2014 ). Current PPARα expression rhythms confirm our previous results ( Gómez-Boronat et al, 2019 ) and are in agreement to those observed in mammals, suggesting preserved functions throughout the phylogeny.…”
Section: Discussionsupporting
confidence: 90%
“…During this resting and fasting states, animals obtain energy from increasing the hepatic fatty oxidation ( Ribas-Latre and Eckel-Mahan, 2016 ), metabolic process that is promoted by PPARα in mammals ( Chen and Yang, 2014 ; Liu et al, 2014 ). Current PPARα expression rhythms confirm our previous results ( Gómez-Boronat et al, 2019 ) and are in agreement to those observed in mammals, suggesting preserved functions throughout the phylogeny.…”
Section: Discussionsupporting
confidence: 90%